Rapid detection of ceftriaxone resistance in clinical isolates of extensively drug resistant Salmonella enterica serovar Typhi - Muhammad Luqman Satti; Faisal Hanif; Ashfaq Hussain; Saman Nadeem; Faryal Younis; Nadia Midhat Zehra (Journal of the Pakistan Medical Association, 2021)
Objective: To see the efficacy of rapid color test for the sensitivity of ceftriaxone against clinical isolates of Salmonella Typhi. Methods: This descriptive cross sectional study was carried out at the department of Microbiology, Pakistan Navy Ship (PNS) Shifa Hospital, Karachi from Nov 2018 through April 2019.We tested 97 clinical isolates of Salmonella Typhi by this rapid color test. All the isolates were also test by conventional disc diffusion method and MICs by Vitek-2 system. Results: Out of these isolates, 83 were ceftriaxone resistant while 14 isolates were ceftriaxone sensitive. Sensitivity and specificity of rapid color test were 100% when compared with results of disc diffusion, E-test and Vitek 2 system. All the results were readable within 2 hours on color test. Conclusion: This color test is rapid, accurate and inexpensive and can be used as a screening test for ceftriaxone resistance in typhoid endemic areas. Keywords: Ceftriaxone; drug resistance; meropenem Continuous...